PERAN EKONOMI ETNIS CINA DI WILAYAH EKS KOTA ADMINISTRATIF JEMBER PADA ZAMAN ORDE BARU DAN AWAL REFORMASI - Winarni, Retno (Historia, 2018)
This article discussed about the role of Chinese ethnics in bussines/trade in the ex administrative city of Jember at yhe New Order and the beginning of reformation Era. The problem is discuss here is why Ninese people succesfully took role in economic and trading sectors. The research method used history method is covers heuristic, critic, interpretation and historiography. Beside the result of the study showed that despite of its minority, Chinese ethnics had dominated the economic and trading sectors in the area of ex Administrative city of Jember during New Orde and beginning of reformation era. Keywords: Chinese; economi and trading; Ex Administrative Jember City; New Order Era; Reformation Era